Metastatic diagnosis of canine sternal lymph nodes using computed tomography characteristics: A retrospective cross‐sectional study. (19th May 2017) - Iwasaki, R.; Murakami, M.; Kawabe, M.; Heishima, K.; Sakai, H.; Mori, T.
Abstract : The accurate evaluation of sternal lymph nodes (StLNs) is critical for the staging of canine thoraco‐abdominal tumours. Computed tomography (CT) provides a non‐invasive means of assessing StLNs, but its diagnostic accuracy for identifying metastases is unclear. In this retrospective cross‐sectional study, we assessed the diagnostic power of various CT measurements. Fifty‐seven dogs that underwent concurrent CT and cytological examination of the StLNs were enrolled retrospectively. The size, shape, X‐ray attenuation and uniformity of the StLNs were assessed. The dogs were divided into metastasis‐negative ( n = 21) and metastasis‐positive ( n = 36) groups. Logistic regression analysis showed that the size (StLN‐to‐second sternebra ratio [ratio‐size]) and precontrast attenuation were significantly different between groups. Combining these parameters achieved a specificity and positive predictive value of 100% (cut‐off values: 1.0, 37.5 Hounsfield units, respectively). This suggests that the combination of ratio‐size and precontrast attenuation is effective for differentiating metastasis to the StLNs on CT.